Vertical Electric Sounding of Leachate Contaminant Plumes at a Dumpsite in Obigbo, Rivers State, Nigeria - W. Tamuno; S. Inichinbia (Journal of Applied Sciences and Environmental Management)
The quality of underground water at a dumpsite in Obigbo, Rivers State, Nigeria, was investigated by collecting 7 vertical electrical soundings (VES) using Wenner electrode configuration with current electrode spacing (AB/2) ranging from 1.0 m to 300 m. Field data were acquired using the SAS 300C resistivity meter and accessories, coordinates and elevation were measured using the Global Positioning System (GPS) at each sounding station. The VES data showed that the area is composed of clay, sandy clay and sand. The contaminated zones have low resistivity and corresponding high conductivity. Two zones were identified, zones of low resistivity and high resistivity with values of 11.3 Ωm to 21.4 Ωm, and 357.0 Ωm to795.0 Ωm respectively. There is thus, both lateral and downward movement of the contaminant leachate plumes. The results also revealed that the  surrounding soil and groundwater around the landfill has not been contaminated to depths exceeding 15.6 m, which is shallower than the productive aquifer depth greater than 37.0 m. Judging from the age of the dumpsite, this site has a good protecting capacity, probably as a result of the presence of sufficient confined layers of clay that have impeded or slowed down the percolation of leachate into the aquifer. The aquifer is the underlying rocks of sand and gravel that are porous which constitute the water body.